Anticipating technical car sequencing rules in the master production scheduling of mixed-model assembly lines - Thorben Krueger; Achim Koberstein; Norbert Bittner (Flexible Services and Manufacturing Journal, 2022)
In this paper, we propose a new linear programming-based approach that enables the consideration of technical car sequencing rules in the master production scheduling of mixed-model assembly lines at a much higher level of detail than previous approaches. To this end, we investigate certain interdependencies of car sequencing rules, which have largely been neglected, both in practice and in the research literature. We illustrate the existence and impact of these interdependencies and show that they induce additional implicit constraints, which can be represented by linear inequalities and incorporated into linear optimization models for master production scheduling. In a numerical study, we evaluate the approach and show, that it can significantly reduce sequencing violations compared to existing approaches.
Keywords: 670; Mixed-model assembly lines; Master production scheduling; Production planning; Car sequencing; Sequencing rules